Efecto de la rentabilidad financiera y operativa en el precio de las acciones de las empresas industriales - Casamayou Calderón, Elisabeth Teresa (2019)
Objective: The study of the research has as objective to determine the simultaneous and independent effect of the financial and operating profitability on the share price (SP) of the companies under study. Method: The design of study is Not experimental with a quantitative approach, the level of the investigation is transversal because it is data has a period of 10 years and correlational because it worth to establish a relationship between the variables. The 34 companies of the industrial sector that are listed on the Lima Stock Exchange were taken into account. For the tabulation of the data, the correlation analysis was carried out after the simple regression model (ROE with PA and ROA with SP) and multiple regression (ROE, ROA with SP), to check the hypotheses the Anova Analysis Anova was used to observe if they influence or not positively, finally the analysis of coefficients was performed to determine the values of the equation of the line. Results: The results obtained are the following: ROE and ROA independently influence positively and explain the behavior of the share price by 27.14% and 26.03%. In the simultaneous analysis of the ROE and ROA on the share price they also positively influence the AP, and explain 21.80% of the behavior of the share price. Conclusions: It is concluded that the behavior of the share price is not a reference of the financial profitability (ROE) nor the operational profitability (ROA) of the companies of the industrial sector analyzed, due to their impact is not significant but positive.